The Role Of Prior Knowledge On Entrepreneurial Alertness Level And Opportunity Recognition In The Field Of Health Entrepreneurship - Elahe Meigounpoory; Mohammadreza Meigounpoory; Ehtesham Seidali Roote (Tehran University of Medical Sciences, 2014)
Background and Aim: Nowadays, entrepreneurs in different fields of health, have an important role in economic development. Prior knowledge has an effect on entrepreneurial alertness and opportunity recognition and with considering the lack of research in this important field, the aim of this study is to evaluate the effect of various aspects of prior knowledge on entrepreneurial alertness & and opportunity recognition .  Materials and Methods: To implement this descriptive-survey study, a questionnaire based on Likert scale sent to 63 active health field managers in east of Tehran, where 52 people responded to the questions. In this study the effect of eight variables of prior knowledge were investigated on entrepreneurial alertness and opportunity recognition. Data were analyzed using SPSS 15 and Spearman correlation test.  Results: Results showed that majori ty of perior knowledge aspects have meaningful relationship to entrepreneurial alertness and opportunity recognition . However, relationship between component of technology skills with both variables was not confirmed. Also, relationship between education level and entrepreneurial alertness, there was no.  Conclusion: Reinforcing of prior knowledge component led to increased entrepreneurship.